Summertime - Laurents, Arthur 1917-2011; Cicognini, Alessandro 1906-1995 (Criterion Collection, 2022)
"With this sublimely bittersweet tale of romantic longing, director David Lean left behind the British soundstage to capture in radiant Technicolor the sun-splashed glory of Venice at the height of summer. In a tour de force of fearless vulnerability, Katharine Hepburn portrays the conflicting emotions that stir the heart of a lonely, middle-aged American tourist who is forced to confront her insecurities when she is drawn into a seemingly impossible affair with a charming Italian shopkeeper (Rossano Brazzi) amid the ancient city’s canals and piazzas. Lean’s personal favorite among his own films, Summertime is an exquisitely tender evocation of the magic and melancholy of a fleeting, not-quite-fairy-tale romance." [criterion.com]
Original: USA 1950
Bildformat 1.37:1
Special Features: New 4K digital restoration, with uncompressed monaural soundtrack on the Blu-ray ; New interview with film historian Melanie Williams ; Interview from 1963 with director David Lean ; Audio excerpts from a 1988 interview with cinematographer Jack Hildyard ; Trailer ; English subtitles for the deaf and hard of hearing ; PLUS: An essay by film critic Stephanie Zacharek ; New cover by Lauren Tamaki
Keywords: Film; Blu-Ray-Disc